2005
DOI: 10.1176/appi.ajp.162.5.924
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Serotonin Transporter Gene With Smoking Behavior

Abstract: There was a highly significant association between SERT and the categorical definition of smoking, irrespective of dependence level, suggesting that this gene influences the initiation of smoking. Mediation analysis failed to substantiate the hypothesis that novelty seeking partially mediates the effect of SERT on smoking. SERT appears to independently contribute to novelty seeking and smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
2
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 33 publications
8
70
2
3
Order By: Relevance
“…56 The results from the population design were confirmed in the family-based analysis. A weak association was observed between Novelty Seeking and the SLC6A4 intron 2 VNTR polymorphism and between Reward and 5-HTTLPR.…”
Section: Allelic Heterogeneitymentioning
confidence: 67%
See 1 more Smart Citation
“…56 The results from the population design were confirmed in the family-based analysis. A weak association was observed between Novelty Seeking and the SLC6A4 intron 2 VNTR polymorphism and between Reward and 5-HTTLPR.…”
Section: Allelic Heterogeneitymentioning
confidence: 67%
“…As discussed below, we have recently examined both SLC6A4 polymorphisms in a study of smoking behavior and personality traits 56 as well as in a molecular genetic study of a musical phenotype.…”
Section: Allelic Heterogeneitymentioning
confidence: 99%
“…21,22 Genotyping Amplification of the RS1, RS3 and AVR microsatellites was achieved using the following primers, as first described by Thibonnier et al Each reaction mixture contained 0.5 mM primer. A ReddyMix master mix was used (Abgene, Surrey, UK) at a magnesium concentration of 1.5-2.5 mM MgCl 2 .…”
Section: Participantsmentioning
confidence: 99%
“…32 The dopaminergic and serotonergic systems have been shown to influence cognitive and motor functions in human and animal studies. 8,10,13,34,35 Neurophysiological studies have shown that listening to music has a strong impact on activity in a network of mesolimbic structures involved in reward processing. 34,35 We have previously studied the association between musical aptitude and creativity in music and the polymorphisms of the DRD2 (plus COMT and TPH1 genes), but did not found an association.…”
Section: Discussionmentioning
confidence: 99%
“…9 Serotoninand dopaminergic systems have been associated with emotional processing. The role of the SLC6A4 polymorphism 5-HTTLPR has previously been studied in reward-seeking behaviors, 10 and in neuropsychiatric conditions. 11-12 SLC6A4 together with AVPR1A polymorphisms have been reported to associate with artistic creativity in professional dancers 13 and with short-term musical memory.…”
Section: Introductionmentioning
confidence: 99%